Anatomical distribution of Rhipicephalus sanguineus sensu stricto (Acari: Ixodidae) on dogs (FAVE Sección Ciencias Veterinarias, 2020)
The anatomical distribution of the different stages of Rhipicephalus sanguineus sensu stricto on canines was analyzed. Data was collected from dogs on monthly sampling during three years in the city of Esperanza, Santa Fe, Argentina. To determine the distribution of the different parasitic stages, the body surface was divided into regions and all specimens were counted in each of them. Larvae had preference for the head followed by the interdigital spaces, ears and abdomen, nymphs were mainly found on ears and abdomen, and other areas of preference were head and interdigital spaces; the adults (males and females) preferred the ears, neck and back.
Keywords: Rhipicephalus sanguineus; brown dog tick; anatomical distribution